Mediation pathways for reduced substance use among parents in South Africa: a randomized controlled trial - Massarwi, AA; Cluver, L; Meinck, F; Doubt, J; Lachman, JM; Shenderovich, Y; Green, O (BioMed Central, 2021)
Background Substance use is a major public health concern worldwide. Alcohol and drug use have increased during recent decades in many low- and middle-income countries, with South Africa, where this study was conducted, having among the highest rates in the world. Despite existing evidence on the effectiveness of family-based interventions in reducing substance use among parents and caregivers in low- and middle-income countries, little is known about the mechanism of change that contributes to the reduction. This study investigated mediators of change in a parenting programme (Parenting for Lifelong Health [PLH]) on reducing substance use among parents and caregivers of adolescents through three potential mediators: parental depression, parenting stress and family poverty. Methods The current study used a pragmatic cluster randomized controlled trial design. The total sample comprised 552 parent and caregiver of adolescents M = 49.37(SD = 14.69) who were recruited from 40 communities in South Africa’s Eastern Cape. Participants completed a structured confidential self-report questionnaire at baseline and a follow-up test 5 to 9 months after the intervention. Structural equation modeling was conducted to investigate direct and indirect effects. Results Analyses indicated that the effect of the PLH intervention on reducing parental substance use was mediated in one indirect pathway: improvement in parental mental health (reduction in parental depression levels). No mediation pathways from the PLH intervention on parental substance use could be associated with parenting stress or family poverty. Conclusions The findings of the study suggest that intervention approaches targeting mental health among parents and caregivers have promise for reducing parental substance use. These findings emphasize the need to create supportive environments and systems for parents who suffer from emotional strain and mental health problems, particularly within families experiencing adversity. Trial registration Pan-African Clinical Trials Registry PACTR201507001119966. Registered on 27 April 2015. The trial can be found by searching for the key word ‘Sinovuyo’ on the Pan-African Clinical Trials Registry website or via the following link: http://www.pactr.org/ATMWeb/appmanager/atm/atmregistry?_nfpb=true&_windowLabel=BasicSearchUpdateController_1&BasicSearchUpdateController_1_actionOverride=%2Fpageflows%2Ftrial%2FbasicSearchUpdate%2FviewTrail&BasicSearchUpdateController_1id=1119